Effectiveness of Soursop (Annona Muricata) Leaf Decoction on Vaginal Discharge Symptoms Among Injectable Hormonal Users: A Quasi-Experimental Study in Makassar, Indonesia - Linda Hardianti Saputri; Safruddin Safruddin; Andi Tenri Abeng; Lutfi Aulia Zulfa (Pancasakti Journal Of Public Health Science And Research, 2026)
Vaginal discharge is one of the common complaints experienced by acceptors of injectable hormonal contraception and may negatively affect reproductive health and quality of life. This study aimed to analyze the effect of soursop leaf (Annona muricata) decoction on reducing vaginal discharge symptoms among injectable hormonal contraceptive acceptors. A quasi-experimental study with a pre-test and post-test two-group design was conducted at the Rappokalling Community Health Center, Makassar, over a period of 10 months. The study involved 50 women of reproductive age who experienced vaginal discharge and were selected using the Slovin formula. Data were collected using observation sheets assessing the color, odor, and itching intensity of vaginal discharge before and after the intervention. Statistical analysis was performed using the Wilcoxon signed-rank test to determine differences before and after administration of soursop leaf decoction. The results demonstrated a significant improvement in vaginal discharge conditions after the intervention (p < 0.05). Respondents with clear white vaginal discharge increased from 54% to 96%, while abnormal vaginal discharge decreased from 46% to 4%. Complaints of unpleasant odor significantly decreased, with respondents reporting no odor increasing from 26% to 84%. Itching symptoms also improved markedly, as moderate itching decreased from 30% to 0%, mild itching decreased from 52% to 16%, and respondents without itching increased from 14% to 84%. These findings indicate that soursop leaf decoction is effective in reducing vaginal discharge symptoms among injectable hormonal contraceptive acceptors and may serve as a complementary non-pharmacological intervention for reproductive health management.